Language Architecture; a Proposal in the Classification of the Elements of Speech Beauty - Davood Mohammadi; Mohammad reza Eslami (مطالعات زبانی و بلاغی)
Although the history of the writing of rhetorical books and the introduction of literary industries in Farsi language is about a thousand years old, the scientific classification of the elements of the beauty of speech in ancient works is not so much known. Researches have been conducted in recent decades in accordance with the view of the new literary currents and the growth of linguistics. However, due to the lack of clarity of the mutual relations between industries, the vagueness of their aesthetic value and the observance of the position of each literary element in the system of the organ like of the work, these classifications have not yet met the expectations of the literary people. In this article, after reviewing and analyzing the old and new rhetoric texts, the "language architecture" approach is proposed for classifying literary industries. This method is based on the association of associate. The language architecture is classified the literary industry in four levels: verbal, semantic, visual, and weight. In this style, you are considering the categorical comprehensiveness, the aesthetic value of the industries, and their role in the structure and axis of the horizontal and vertical poetry and the formation of the language system and the specific mental geometry of each poet. The results of this research are a small step in explaining the architecture of language and the association study in the field of Persian literature, especially poetry.